Combining interferon-γ release assays with lymphocyte enumeration for diagnosis of Mycobacterium tuberculosis infection. Issue 6 (June 2020) - Lv, Dingfeng; Liu, Yanqing; Guo, Fei; Wu, Aihua; Mo, Yijun; Wang, Shanshan; Chu, Jinguo
Objective: To investigate the possibility of combining tuberculosis (TB)-interferon (IFN)-γ release assays (IGRAs) with lymphocyte enumeration for diagnosis of Mycobacterium tuberculosis infection. Methods: We performed a retrospective study of 166 TB patients [68 patients with pulmonary tuberculosis TB (PTB) and 98 patients with extra-pulmonary TB (EPTB)] diagnosed in our hospital between January 2016 and May 2018 along with 377 non-TB patients. The diagnostic performance of the TB-IGRA was evaluated using receiver operating characteristic (ROC) curves. Youden's index was used to determine the optimal cut-off threshold. Results: IFN-γ release in patients with PTB and EPTB were dramatically higher compared with non-TB patients (203.58±18.00 pg/mL, 201.83±14.56 pg/mL and 32.12±4.36 pg/mL, respectively). IFN-γ release was positively correlated with lymphocyte counts and percentages in patients with PTB (r = 0.252 and r = 0.278, respectively) and EPTB (r = 0.229 and r = 0.298, respectively). No correlation was observed in non-TB patients. The area under the ROC curve for TB-IGRA was 0.884. When the optimal cut-off value for IFN-γ (14 pg/mL, Youden's index 0.661) was applied, the sensitivity was 88.6% and the specificity was 77.5%. Conclusions: Combining TB-IGRA with lymphocyte enumeration was effective for diagnosis of early-stage Mycobacterium tuberculosis infection.